Kajian Biblika Kebebasan Finansial Alkitabiah - Jhon Leonardo Presley Purba; Priyantoro Widodo (Manna Rafflesia, 2021)
Finance is an important aspect of human life, so having financial freedom is the hope of many people. But poor financial management often makes a person depressed and frustrated. For Christians, the topic of discussion about money and its management is also often considered taboo and has worldly connotations. But in fact, the Bible has a lot to say about money and the principles of its management. The purpose of this study is to build a biblical study of financial freedom by explaining biblical principles on financial management to gain financial freedom. This research is presented in a qualitative-descriptive form through a topical presentation on finance to conduct a study and theological construction of Biblical financial freedom. The data collection and analysis model used is a literature study. Biblical financial freedom is a construction of financial management based on biblical principles. The results of this study a person can have the right heart and morals in managing finances wisely and well, refrain from falling into debt and credit bonds, use the money to help others in need, dedicate all money and wealth to the glory of God with good management. , true, obedient, and faithful to tithe.